2002
DOI: 10.1530/eje.0.1470503
|View full text |Cite|
|
Sign up to set email alerts
|

Apolipoprotein E gene determines serum testosterone and dehydroepiandrosterone levels in postmenopausal women

Abstract: Objective: Apolipoprotein E (ApoE) is believed to play an important role in lipid metabolism and has been found to be related to diseases associated with ageing, the important characteristic of which is decline in circulating sex steroids, including androgen. Design: To find the relationships of levels of serum testosterone and its precursor, dehydroepiandrosterone (DHEA), to ApoE polymorphism in 113 postmenopausal Caucasian women. Methods: The ApoE genotype was assessed by polymerase chain reaction and CfoI e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 11 publications
1
16
0
1
Order By: Relevance
“…ApoE expression may influence HPA axis function, as it has been implicated as a modulator of steroidogenesis in the adrenal gland (Reyland et al, 1991;Thorngate et al, 2002;Zofková et al, 2002). In plasma, E2/E2 mice had markedly elevated apoE concentrations.…”
Section: Neuroendocrine and Physiological Alterations In E2+ Mice Folmentioning
confidence: 99%
“…ApoE expression may influence HPA axis function, as it has been implicated as a modulator of steroidogenesis in the adrenal gland (Reyland et al, 1991;Thorngate et al, 2002;Zofková et al, 2002). In plasma, E2/E2 mice had markedly elevated apoE concentrations.…”
Section: Neuroendocrine and Physiological Alterations In E2+ Mice Folmentioning
confidence: 99%
“…Why was there no change in ovarian TC and TG concentrations, despite the presence of more lipid in the ovaries of Apoe K/K mice? In fact, although APOE is the most important supplier of the cholesterol precursor for steroid hormone production in steroidogenic tissues, it is unrelated to extracellular lipid transport (Mahley & Rall 2000, Zofkova et al 2002. The lipid droplets appear to be complex, metabolically active organelles that are directly involved in membrane traffic and possibly phospholipid recycling.…”
Section: Discussionmentioning
confidence: 99%
“…Quite surprisingly, the mean value of the central obesity indicator (WHR) was lower in the APOE*4 carriers. Based on results of a cross-sectional study of 113 Caucasian postmenopausal women aged 62.4±9.8 years published by Zofkova et al [29], women possessing the APOE*4 allele had significantly higher serum testosterone and dehydroepiandrosterone (DHEA) levels than those lacking the APOE*4 allele. Studies have reported that dehydroepiandrosterone-S (DHEA-S, DHEA metabolite) levels are higher in lean women than in obese ones [30,31].…”
Section: Discussionmentioning
confidence: 99%